Violation of the Child Vaccination Calendar: the Attitudes of Doctors and Parents - T. V. Kulichenko; M. N. Dymshits; M. A. Lazareva; A. R. Babayan; E. G. Bokuchava (Union of pediatricians of Russia, 2015)
The aim of this publication is a comparative analysis of the attitudes of paediatricians and parents towards vaccination and the vaccination calendar.Methods. An online poll among mothers of children under the age of was carried out. 315 women at the age of 20-45 took part in the poll. They were all questioned about their attitude towards vaccination and the adherence to the vaccination calendar. 42 paediatricians contributed their opinion on the subject of vaccination calendar violations, unjustified medical rejections and the vaccination of their own children and themselves.Results. The poll revealed a lack of correspondence between the parents' idea of vaccination and the paediatricians' attitudes towards vaccination calendar violations.Conclusion. Educational programs for doctors and parents covering the topic of vaccination can provide an effective resistance to the present anti-vaccination lobby. At the moment, the key issues are the necessity to decrease unjustified medical rejections for vaccinations, a continuous attention to the child's vaccination status (at any addressing) and informing the parents about the diseases which can be prevented through immunization.